OP56 Differential Effects of Smoking Cessation During Pregnancy on Birth Weight in a Cohort of Disadvantaged Women. (17th September 2012) - Hayes, CB; Kearney, M; Collins, C; O'Carroll, H; Wyse, E; Geary, M; Kelleher, CC
Abstract : Background: Smoking during pregnancy is recognized as the most important preventable risk factor. Maternal smoking accounts for 20–30% of low birth weight infants (<2, 500g), the most common adverse outcome in pregnancy. The objective of this study was to explore the effects of maternal smoking habits: stopping smoking in the first and second trimesters, continuing to smoke, number of cigarettes smoked and socio-demographic factors on infant birth weight. Methods: The study was a longitudinal cohort study of 1, 000 pregnant smokers attending public hospital clinics in a disadvantaged catchment area at first pre-natal visit (V1), and assessed at 28–32 weeks (V2) and at one week after birth (V3) using an interviewer-administered questionnaire. The primary outcome variables were: change in smoking status based on self-reported response and urinary cotinine measurement for those who had quit. ANOVA was carried out to test for differences in mean birth weight. A multiple regression analysis with birth weight as the dependent variable was carried out on demographic and smoking characteristics and derived smoking category variables at V3: sustained quitters, continued smokers, successful quitters at V3 and intermittent quitters. Results: The mean difference in birth weight between continued smokers and sustained quitters was significant, (mean difference = 233g, 95% CI=60 – 406g, p=0.008), as was the difference between continued smokers and intermittent quitters (mean difference = 202g, 95% CI =17 – 386g, p=0.03). Regression on baseline variables showed that only 2.4% of the variance (R 2 ) was explained by smoking characteristics; that is, number of smokers in the home other than self or partner (p=0.008) and number of cigarettes smoked per day (p=0.02). A second regression model showed gestation at delivery to be the best predictor of birth weight (R 2 =44.2). The number of cigarettes smoked at V2 explained an additional 2.1% (p<0.001) and being a sustained quitter 0.5% (p=0.02). Conclusion: In this study a clear gradient was observed around smoking behaviour and birth weight with continued smokers having infants with lowest birth weights, sustained quitters the highest and intermittent quitters somewhere in between. The study also demonstrated that the negative effects of maternal smoking on birth weight are at least partly reversible. It thus showed a beneficial effect of quitting smoking for at least part of pregnancy and a link between passive smoking and birth weight. These findings are important for the delivery of targeted health promotion messages to smoking women in early pregnancy.